Effects of Audit Committee Diversity on Financial Reporting Quality among Consumer Goods Companies in Nigeria: Array - Olowookere, Johnson Kolawole; Oyewole, Olabode Michael; Lamidi, Wasiu Adebayo (The Journal of Accounting and Management, 2021)
This study looked at the effect of gender diversity on financial reporting performance on audit committees. All twenty (20) consumer goods companies listed on the Nigerian Stock Exchange are included in the current study demographic. From 2009 to 2019, the study used a purposive sampling methodology to classify all thirteen (13) consumer goods companies that published annual periodic reports. The study utilizes STATA 15 tools to analyse evidence and clinical methods like heteroskedasticity and multicollinearity. After that, regression analysis was used to look into the effect of audit committee diversity on financial reporting performance. The analysis revealed that having a diverse audit committee increases financial reporting performance. As a consequence, the findings suggest that the makeup of audit committees be managed to ensure gender diversity in order to increase monitoring performance